(untitled) (CIPEEX, 2026)
Brazil is one of the world’s largest consumers of pesticides, and exposure to these compounds has been associated with chronic adverse effects, including cancer. This study investigates the relationship between agrochemical use and the incidence of breast and cervical cancer in the population of the Southwest I and Southwest II health regions of Goiás, between 2010 and 2025. Objective: To analyze, based on secondary data, the incidence and mortality of these cancers in agricultural regions with high pesticide use. Method: Data on incidence and mortality were collected from INCA, DATASUS, IBGE, SIM, and SINAN, as well as IBAMA reports on pesticide marketing. The literature review included articles indexed in PubMed, SCIELO, and BVSalud. Results: In Brazil, between 2023 and 2025, an estimated 73,610 new cases of breast cancer and 17,010 cases of cervical cancer were reported annually. In Goiás, adjusted rates exceeded the national average. Municipalities such as Castelândia and Porteirão had rates much higher than the state average, indicating inequalities in access to screening and diagnosis. The state sold 56,857 tons of pesticides in 2023, with glyphosate, atrazine, and chlorpyrifos—classified as probable or possible carcinogens—standing out. Conclusion: The analysis suggests that environmental exposure to pesticides may contribute to a higher risk of breast and possibly cervical cancer in Goiás. This scenario highlights the need for stricter public policies to regulate pesticide use, expanded preventive strategies, and additional epidemiological investigations.